2020
DOI: 10.3390/nu12020442
|View full text |Cite
|
Sign up to set email alerts
|

Affective and Enjoyment Responses to Short-Term High-Intensity Interval Training with Low-Carbohydrate Diet in Overweight Young Women

Abstract: Low-carbohydrate diets (LCs) seem effective on weight reduction and maintenance. However, the affect and enjoyment of exercise during LCs is not clear. The purpose of the present study was to compare the psychological responses to high-intensity interval training (HIIT) and to moderate-intensity continuous training (MICT) during the consumption of a 4-week LC diet in overweight young women. With LCs (~10% carbohydrate, 65%-70% fat, 20%-25% protein), forty-three eligible women (age: 20.9 ± 3.1 years; body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
5
2
Order By: Relevance
“…Besides the muscle constraints generated by HIIE (higher velocity and intensity performed), the fact that women performed the sessions in fasting conditions could have made HIIE more difficult, due to higher glycogen and plasma glucose utilization. 40 However, we did not find any effect of HIIE or MICE on glycemia during or after exercise. Finally, despite higher rates of perceived exertion in HIIE 1 and HIIE 2 vs. MICE, enjoyment was similar for all three modalities, thus confirming the feasibility of such programs in this population.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Besides the muscle constraints generated by HIIE (higher velocity and intensity performed), the fact that women performed the sessions in fasting conditions could have made HIIE more difficult, due to higher glycogen and plasma glucose utilization. 40 However, we did not find any effect of HIIE or MICE on glycemia during or after exercise. Finally, despite higher rates of perceived exertion in HIIE 1 and HIIE 2 vs. MICE, enjoyment was similar for all three modalities, thus confirming the feasibility of such programs in this population.…”
Section: Discussioncontrasting
confidence: 69%
“…In our study, the rate of perceived exertion increased throughout exercise, but was higher during HIIE 1 and HIIE 2 than MICE. Besides the muscle constraints generated by HIIE (higher velocity and intensity performed), the fact that women performed the sessions in fasting conditions could have made HIIE more difficult, due to higher glycogen and plasma glucose utilization 40 . However, we did not find any effect of HIIE or MICE on glycemia during or after exercise.…”
Section: Discussioncontrasting
confidence: 62%
“…However, based on existing data with contradictory results in the literature [14,33,38], there is still no solid evidence to draw conclusions. Individual differences in physical (e.g., physical activity level [39]), psychological status (e.g., exercise preference and tolerance of intensity) [40,41], and macronutrient intake (e.g., low-carbohydrate diets) [42] also account for the discrepancy. From the aspect of the neural system, the interplay of prefrontal cortex and amygdala have been revealed to regulate affective responses during exercise [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 24 , 25 It was evidenced that enjoyment progressively increased following HIIT with repeated measurements over a period of 4–8 weeks. 24 , 26 , 27 , 28 , 29 However, few studies have analysed the long-term effects of HIIT (i.e., ≥12 weeks) on enjoyment and pleasure. To the best of our knowledge, only one study (Hu et al., 2021) examined the effects of 12-week interval protocols and found that interval training caused the same exercise enjoyment as MICT in overweight young women.…”
Section: Introductionmentioning
confidence: 99%